The Influence of BLACKPINK as A Brand Ambassador to The Purchase Intention at Shopee - Johana, Engrasia Putri; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The research was taken under the title The Influence of BLACKPINK as a Brand Ambassador to Purchase Intentions at Shopee because researcher sees Shopee as an e-commerce that usually uses brand ambassadors to attract the consumer’s interest. One of their brand ambassadors is BLACKPINK. BLACKPINK is a Korean girl group that famous since their debut in 2016 by the power and the stronger on their character. Because of this Shopee sees opportunities from the spread of Korean pop or K-pop culture in all walks of life. So, the purpose of this study is to find out how much the influence of brand ambassadors have on increased buying interest in Shopee. the research used qualitative approach by having an interview with 4 interviewees and 4 previous research papers to find out the reasons and effects they felt during BLACKPINK becoming Shopee's brand ambassador. The research found that previous success during BLACKPINK's time as a brand ambassador was due to the event and supported there was a free shipping voucher given by Shopee to attract purchases.